2013
DOI: 10.1182/blood.v122.21.2907.2907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Afuresertib, An Oral Pan-AKT Inhibitor, In Patients With Langerhans Cell Histiocytosis

Abstract: Background Langerhans cell histiocytosis (LCH) is a heterogeneous disease whose myriad manifestations result from accumulation of Langerhans cells in a variety of organs most commonly including skin, bone, central nervous system, liver, lymph nodes, and bone marrow. The disease can affect people of any age. Treatment is primarily driven by disease extent and organ involvement and can range from focused radiation or surgery to multi-agent chemotherapy. There is a relatively high recurrence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While the latter inhibits AKT activation and phosphorylation by altering the chemical structure of the AKT PH structural domain, thereby preventing AKT localization on the cell membrane. AKT competitive inhibitors are majorly listed below: Capivasertib (AZD5363) 71 , a selective PAN-AKT inhibitor that entered clinical trials for the treatment of breast, gastric, and prostate cancers; Afuresertib (GSK2110183) 72 , a monotherapy of relapsed or refractory multiple myeloma treatment; Uprosertib (GSK2141795), which remains in phase Ⅰ and Ⅱ studies 73 ; and the AKT inhibitor Ipatasertib (GDC-0068, RG7440), a monotherapy for the treatment of triple-negative breast cancer, still being in phase Ⅰ and Ⅱ studies 74 . Perifosine as an inhibitor of AKT metaplasia to inhibit neuroblastoma tumor cell growth has entered phase Ⅱ studies 75 .…”
Section: Value-added Regulation Of Tumor Cells By Pi3k/akt/mtor Pathw...mentioning
confidence: 99%
“…While the latter inhibits AKT activation and phosphorylation by altering the chemical structure of the AKT PH structural domain, thereby preventing AKT localization on the cell membrane. AKT competitive inhibitors are majorly listed below: Capivasertib (AZD5363) 71 , a selective PAN-AKT inhibitor that entered clinical trials for the treatment of breast, gastric, and prostate cancers; Afuresertib (GSK2110183) 72 , a monotherapy of relapsed or refractory multiple myeloma treatment; Uprosertib (GSK2141795), which remains in phase Ⅰ and Ⅱ studies 73 ; and the AKT inhibitor Ipatasertib (GDC-0068, RG7440), a monotherapy for the treatment of triple-negative breast cancer, still being in phase Ⅰ and Ⅱ studies 74 . Perifosine as an inhibitor of AKT metaplasia to inhibit neuroblastoma tumor cell growth has entered phase Ⅱ studies 75 .…”
Section: Value-added Regulation Of Tumor Cells By Pi3k/akt/mtor Pathw...mentioning
confidence: 99%
“…But we also chose it because, when these experiments were being planned, a case report had appeared which described a major clinical response to an AKT inhibitor in an LCH patient. [46] However, a clinical trial of the inhibitor in LCH patients showed minimal activity[47] and further genetic analysis of a large number of LCH cases showed only rare disruption or alteration of the PTEN/AKT/PIK3C pathway. [4, 5, 48] In fact, very few LCH cases with alterations in MAP kinase pathway genes show genetic alterations affecting other pathways.…”
Section: Discussionmentioning
confidence: 99%